2000
DOI: 10.1002/1098-2388(200007/08)19:1<42::aid-ssu7>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreductive surgery for advanced stages of ovarian cancer

Abstract: During the past two decades, maximum cytoreductive surgery (also called debulking surgery) has been the recommended surgical approach for advanced stages of ovarian carcinoma. The residual tumor volume after surgery is one of the strongest prognostic factors, and only patients who undergo complete or optimal surgery are likely to be long‐term survivors (i.e., 50% after five years). A well‐trained surgeon in the field of gynecologic oncology can achieve an optimal tumor reduction in up to 75% of patients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 54 publications
5
52
0
2
Order By: Relevance
“…Systemic therapies are more likely to be effective after maximal tumor debulking because, with a given cell kill rate, fewer cells will survive, and evolution of resistant cells will be less probable [16,17]. For this reason and also to control the disease locally, mastectomy was performed in the antracycline-resistant eight patients in the synchronous group.…”
Section: Resultsmentioning
confidence: 99%
“…Systemic therapies are more likely to be effective after maximal tumor debulking because, with a given cell kill rate, fewer cells will survive, and evolution of resistant cells will be less probable [16,17]. For this reason and also to control the disease locally, mastectomy was performed in the antracycline-resistant eight patients in the synchronous group.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies suggested that patients of advanced ovarian cancer treated with NAC improved performance status, decreased the extent and morbidity of surgery, and increased the opportunity of optimal debulking surgery [2,[4][5][6][7][8][10][11][12]. Therefore, it is natural to consider NAC followed by IDS to be an alternative to conventional PDS in treating advanced ovarian cancer and expect that the NAC group would have better survival than PDS group.…”
Section: Discussionmentioning
confidence: 99%
“…Disappointingly, optimal debulking can be achieved in only 30-60 % of stage III/IV ovarian cancers [2]. Most patients diagnosed with advanced ovarian cancer are elderly, with multiple comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with advanced ovarian cancer are usually low candidates for primary surgery due to massive ascites, pleural effusion, and large abdominal tumor. In these patients, sometimes the tumor is unresectable [8][9][10].…”
Section: Introductionmentioning
confidence: 99%